Pencegahan Stunting Pada Anak Usia Dini dan Ibu Hamil Melalui Pembudidayaan Daun Kelor di Desa Cikurutug, Kecamatan Cireunghas - Supindar, Hadi Rachmat; Dianti, Putri Rachmah; Rahma, Indriani (Jurnal Surya, 2023)
Community Development Participation is one of the activities carried out as community service which is one of the Catur Dharma Colleges of Muhammadiyah. The UMMI 13 KKN-T student creativity program aims to prevent stunting in early childhood through counseling and cultivating Moringa leaves in Cikurutug village, Cireunghas sub-district. This program focuses on health education and empowering local communities to overcome the problem of malnutrition by involving various collaborative activities.